Pengaruh Kemasan Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Pada UKM Maleo Lampung - Hidayat, Taufik; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2022)
ABSTRACT Taufik Hidayat. 16610154. The Effect of Packaging And Product Quality on Product Purchasing Decisions At UKM Maleo Lampung. An Undergraduate Thesis. Management Study Program. Faculty of Economics and Business. MuhammadiyahUniversity of Metro. Advisor: (1) Dr. H. Febriyanto, S.E., M.M. (2) H. Suwarto, S.E., M.M. The development of the business for poultry needs, namely birds, has made the competition in this industry even more challenging. So, that Maleo SMEs can succeed in competition, they must try to create and retain customers to achieve the goal. The company must produce products that consumers want with attractive packaging and good quality. Thus it must be able to understand the behaviour of target consumers to increase product sales to SMEs. Maleo. This study aimed to determine the effect of packaging and product quality on product purchasing decisions at UKM Maleo, Lampung. This was done to solve the problem of how the business that has been run can continue to grow and run successfully in a competitive environment to achieve the desired profit. The type of research used in this research is quantitative research. A quantitative research method is one type of research whose specifications are systematic, planned and structured from the beginning to the making of the research design. The results of the research packaging have a negative and insignificant effect on purchasing decisions at UKM Maleo, Lampung. Product quality has a positive and significant effect on purchasing decisions at UKM Maleo, Lampung. Together, packaging and product qualitypositively and significantly impact purchasing decisions at UKM Maleo, Lampung.